2022
DOI: 10.1111/ppc.13034
|View full text |Cite
|
Sign up to set email alerts
|

Determining the relationship between spirituality and perceptions of care in nursing students: A cross‐sectional study

Abstract: Background Caring is a core value in nursing education and many of its features can be measured as specific behaviors. It is not clear how nurses' spirituality affects their caring behavior. Purpose The aim of this study was to investigate the relationship between spirituality and spiritual care and nursing students' perceptions of care. Design and Methods This was a descriptive cross‐sectional study. The study sample consisted of 467 students in the nursing department of a university in Northeastern Anatolia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…27 Another study found students' care assessments to be partially adequate, recommending further training on the topic. 28 It can be inferred that factors like clinical application and the guidance of an instructor positively influence care perception.…”
Section: Discussionmentioning
confidence: 99%
“…27 Another study found students' care assessments to be partially adequate, recommending further training on the topic. 28 It can be inferred that factors like clinical application and the guidance of an instructor positively influence care perception.…”
Section: Discussionmentioning
confidence: 99%